A good life : human rights and encounters with modernity - Edmunds, Mary, 1943- (ANU E Press, 2013)
"This is a book about hope, the hope that we have ways to live together in a rapidly changing world which will enable us to live a good life in the modern world. It goes beyond hope and suggests how we may do this"--Foreword